A comparative study of university students’ responses in the first and second COVID-19 pandemic waves - Podlogar, Neža (Psihološka obzorja (Ljubljana), 2022)
The COVID-19 pandemic also affected the university setting, where the study process was conducted remotely for the first time. In our research, we were interested in how students of the Faculty of Education of the University of Ljubljana reacted to the changed emergency situation, both emotionally and cognitively. A total of 291 students participated in the study during the first pandemic wave and 382 students during the second pandemic wave. The aim of the study was to examine their views on emergency remote teaching, their psychosocial experience of the overall situation, self-regulation strategies used in distance learning and positivity. Although the overall psychosocial experience and positivity were comparable in the first and second waves of the pandemic, the emergency remote education in the second wave suited the students better. In the second wave, students reported fewer problems with the organisation of time and space, planning study work, in-depth study work, product quality and efficiency, but more problems with concentration and communication with classmates. Most self-regulation strategies were used to a similar extent. Differences emerged in two self-regulation strategies: in the second wave, students used time management to a lesser extent, but used help-seeking strategies more frequently than students in the first wave. The research findings contribute to a better understanding of the different experiences of students at different periods of the pandemic and provide professionals with an opportunity to focus on the critical elements when looking for ways to support students during emergency remote teaching in the pandemic.
Keywords: COVID-19; duševno zdravje; izobraževanje; pouk na daljavo; šolska klima; Študenti; učenci; Višje in visokošolsko izobraževanje; vzgoja